2010
DOI: 10.3171/2010.2.focus1026
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty complications following wartime decompressive craniectomy

Abstract: Object In support of Operation Iraqi Freedom (OIF) and Operation Enduring Freedom-Afghanistan (OEF-A), military neurosurgeons in the combat theater are faced with the daunting task of stabilizing patients in such a way as to prevent irreversible neurological injury from cerebral edema while simultaneously allowing for prolonged transport stateside (5000–7000 miles). It is in this setting that decompressive craniectomy has become a mainstay of far-forward neurosurgical management of traumatic brain injury (TBI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 16 publications
1
56
1
4
Order By: Relevance
“…1). We defined EFC as low density fluid in the epidural space on brain CT scan Data from recent studies have indicated that cranioplasty following decompressive craniectomy was associated with a high complication rates, ranged from 16.4% to 34% 4,6,8,12) . However, these studies mainly analyzed on major complications including infection, hematoma formation, and bone flap resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We defined EFC as low density fluid in the epidural space on brain CT scan Data from recent studies have indicated that cranioplasty following decompressive craniectomy was associated with a high complication rates, ranged from 16.4% to 34% 4,6,8,12) . However, these studies mainly analyzed on major complications including infection, hematoma formation, and bone flap resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The complications, including infection, hematoma, and bone graft resorption following cranioplasty have been well studied and considered as a significant cause of postoperative morbidity 6,8,11,12) . However, reports of epidural fluid collection (EFC) after cranioplasty are uncommon and limited to isolated case examples and small series 6,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Modern blast explosions create cavitary injuries that extend past the border of the surface wound, often creating both soft-tissue and cranial defects. 28 However, advances in armor and immediate damage control with neurosurgery have resulted in more soldiers surviving such blast injuries. Currently, immediate treatment includes aggressive decompressive craniectomy, conservative brain debridement, and a watertight dural repair.…”
Section: Recent Conflictsmentioning
confidence: 99%
“…At a later time, a custom plate is implanted over the cranial defect. 16,28 More simple cranial defects can be repaired in a single-stage procedure.…”
Section: Recent Conflictsmentioning
confidence: 99%
“…13,32,33 Decompressive craniectomy carries a complication risk of 37%-50%, 5,13,32,79 and patients undergoing a cranioplasty for the repair of a craniectomy defect face an additional 16%-34% complication risk. 3,9,14,23,24,46,57,65,75 One caveat regarding the DECRA trial is that only patients without any significant mass lesions were enrolled. 13 Some studies seem to suggest that a craniectomy may improve outcome when used for the treatment of elevated ICP associated with a mass lesion.…”
mentioning
confidence: 99%